From Retroviridae to Flaviviridae: adventures in molecular virology - Butler, Molly, author; Rovnak, Joel, advisor; Quackenbush, Sandra, committee member; Stenglein, Mark, committee member; Moreno, Julie, committee member (Colorado State University. Libraries, 2021)
The work presented here encompasses two avenues of investigation: the first, regarding the identification of a novel retrovirus in Gunnison's prairie dogs, and the second regarding the role of cyclin-dependent kinases 8 and 19 (CDK8 and CDK19) as transcriptional regulators during infection with dengue virus serotype 2 (DENV2) and during the innate immune response. Part I: During the course of research and wildlife disease surveillance efforts, we identified three cases of thymic lymphoma in free-ranging Gunnison's prairie dogs (Cynomys gunnisoni). As Gunnison's prairie dogs are keystone species, that is, critical for the maintenance of their ecosystems, we investigated the potential for an association between the observed thymic lymphomas and retroviral infection. We identified a novel retroviral sequence which exhibits genetic organization consistent with a type D betaretrovirus and which was highly associated with thymic lymphoma in Gunnison's prairie dogs. The proposed name of this virus is Gunnison's prairie dog retrovirus (GPDRV). Part II: CDK8 and CDK19 are transcriptional regulators which are critical for modulating gene expression changes during induced states such as hypoxia and starvation. We investigated the role of CDK8 and CDK19 in two distinct but related induced states: infection with DENV2 and the type I interferon response. We found that in the context of DENV2 infection, CDK8/19 regulate metabolic gene expression changes, the result of which is a reshaping of the host cell metabolic environment which is ultimately beneficial to viral replication. Therefore, chemical inhibition or reduced expression of CDK8 or CDK19 significantly restricted viral replication. Both within the context of DENV2 infection and with non-viral stimulation of innate immunity, we identified a role for CDK8 and CDK19 as regulators of the type I interferon response. CDK8 and CDK19 have distinct and overlapping functions as regulators of IFN-β expression dependent on the nature of the stimulus. This work not only furthers our understanding of host transcriptional regulation during DENV2 infection and within innate immunity, but also the diverse and complex functions of CDK8 and CDK19 as key modulators of cellular stress responses.
Keywords: Cynomys gunnisoni; Thymic lymphoma; type I interferon; dengue; CDK8; transcription